2015
DOI: 10.1159/000441415
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans Cell Histiocytosis of the Clavicle in an Adult: A Case Report and Review of the Literature

Abstract: Langerhans cell histiocytosis (LCH) usually occurs in children under the age of 10 years with a predilection for the skull, spine, rib and humerus. Solitary LCH occurring in an adult clavicle is uncommon with limited reports to date. The lesion in our patient was curetted with the intent to make a diagnosis, which subsequently lead to the remission of the symptom and the disease. At the final follow-up after 1 year, no local recurrence or metastasis is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The chest wall, particularly the clavicle and sternum, was the second most common site involved after the skull. We could not find exact data on clavicular involvement, but some studies have reported its incidence in LCH disease [ 7 , 9 , 37 – 39 ]. Consistent with the findings of these studies, we only found five cases of clavicular involvement.…”
Section: Discussionmentioning
confidence: 94%
“…The chest wall, particularly the clavicle and sternum, was the second most common site involved after the skull. We could not find exact data on clavicular involvement, but some studies have reported its incidence in LCH disease [ 7 , 9 , 37 – 39 ]. Consistent with the findings of these studies, we only found five cases of clavicular involvement.…”
Section: Discussionmentioning
confidence: 94%
“…The typical imaging findings of LCH flat and irregular bone lesions reported in the literature are mainly dilated or lytic bone destruction. Rib lesions are often accompanied by pathological fractures, and soft tissue extension may cause extrapleural masses [ 24 , 25 ]. In our series, only 21.4% (3/14) of the cases were associated with pathological fractures, and 35.7% (5/14) were associated with soft tissue masses.…”
Section: Discussionmentioning
confidence: 99%
“…In cases that Ukada et al reported in 2015, symptoms were relieved by bone curettage combined with biopsy [ 13 ] and in cases Shaowu et al reported in 2014, internal fixation with plate was performed on clavicles in addition to bone curettage with biopsy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%